Możliwość zastosowania narzędzi rachunkowości zarządczej w szpitalu - Zaleska, Beata (Possibilities of Application of Managerial Accounting in a Hospital, 2007)
Managerial accounting should provide all the managerial processes of a hospital: from planning, organization and motivating, to supervision. The information provided should make it possible achieve the goal as set by a healthcare unit, which is help to maintain and improve the health condition of the society. For those hospitals which operate on the competitive market of medical services, such economic objectives are important as effectiveness, a rational use of the resources, limitation of the debt, as well as social objectives (an effective provision of medical services on the highest quality level possible which facilitates an increased satisfaction on the part of patients, payees and establishing bodies). The article briefly presents the most useful (in the author's opinion) managerial accounting tools.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 537-548